Clinical application of metagenomic next-generation sequencing in tuberculosis diagnosis - Liu, Ying; Wang, Huifen; Li, Yaoguang; Yu, Zujiang (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract Objective: The purpose of this study was to evaluate the clinical diagnostic value of metagenomic next-generation sequencing (mNGS) for tuberculosis. Methods: mNGS, targeted PCR, acid-fast staining, T-SPOT.TB assay and pathological examination were performed on the specimen. Based on the final clinical diagnosis of tuberculosis (TB), the accuracy of mNGS diagnosis was calculated. The diagnostic accuracy of mNGS was compared with that of targeted PCR, T-SPOT.TB assay and the clinical final diagnosis. Pathological tests were performed when necessary. Results: In total, 52 patients with suspected of TB in this study were included in the analysis. 14 (26.9%) cases were positive for acid-fast staining. The positive rate of T-SPOT.TB assay in 52 patients was 73.1% (38/52). Among 52 patients, 39 (75%) were detected positive for Mycobacterium tuberculosis (MTB) by mNGS, and the detection rate of mNGS was almost consistent with the positive rate of T-SPOT.TB assay. Regarding the detection rate of M. tuberculosis, mNGS were as high as 75% (39/52), whereas acid-resistant staining was only 26.9% (14/52), which showed a statistically significant difference (p<0.05). Of the 39 positive mNGS reports, 31 (79.5%) cases were consistent with the clinical diagnosis. The diagnostic rate of acid-fast staining in 31 cases with confirmed TB was 51.6% (16/31), which was far lower than 100% (31/31) of mNGS. The positive rate of T-SPOT.TB assay was 90.3% (28/31), also lower than 100% of mNGS. PCR was performed in 24 out of 39 mNGS-positive specimens, where 18 (75%) were positive and 6 (25%) were negative. Conclusions: The mNGS has a higher detection rate for M. tuberculosis than the traditional method of PCR and acid-fast staining. As an adjunctive diagnostic technology, mNGS can be combined with traditional detection methods to play a guiding role in the diagnosis and treatment of TB.